Pemanfaatan Terapi Komplementer untuk Mengurangi Mual Muntah pada Ibu Hamil Trimester I - Irma Maya Puspita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: One of the signs pregnant women suffer in the first trimester is nausea and vomiting, which hyperemesis gravidarum can even exacerbate. Symptoms of nausea and vomiting during pregnancy can be overcome pharmacologically and non-pharmacologically. One of the non-pharmacological therapies that are simple, inexpensive, effective, and without adverse side effects is acupressure or massage at point 6 of the pericardium. This report aims to provide midwifery care to pregnant women with complementary acupressure therapy to reduce nausea and vomiting.Methods: This research is a quasi-experimental one-group pre-test and pre-test design. The sample of this study was 30 pregnant women who experienced emesis gravidarum at PKU Muhammadiyah Hospital Surabaya. The sampling technique in this study was carried out using proportional total sampling. This research was conducted from March to July 2019. The research instrument used the RINVR questionnaire.Results: The study’s results are related to the calculation of the A.symp.sig nausea score. (2-tailed) obtained a value of 0.005 <0.05, which indicates that there is a significant difference between the results of the post-test and the results of the pre-test. Vomiting score calculation obtained by Asymp.sig. (2-tailed) obtained a value of 0.004 <0.05, which indicates that there is a significant difference between the results of the post-test and the results of the pre-test. Calculation of nausea vomiting scores obtained Asymp.sig. (2-tailed) obtained a value of 0.005 <0.05, which indicates that there is a significant difference between the results of the post-test and the results of the pre-test. Calculation of the total score obtained Asymp.sig. (2-tailed) obtained a value of 0.005 <0.05, which indicates that there is a significant difference between the results of the post-test and the results of the pre-test.Conclusion: Based on the study’s results, it was found that complementary acupressure therapy effectively treats nausea and vomiting (emesis gravidarum) in first-trimester pregnant women at PKU Muhammadiyah Hospital Surabaya. Therefore health workers can apply acupressure in midwifery care, especially in reducing nausea and vomiting in pregnant women in the first trimester.